KEBERADAAN INSTRUMEN ELEKTRONIK DALAM MENGUNGKAPKAN TINDAK PIDANA - Hendra, Hendra; Nopianti, Nia; Roni, Abdul (Solusi, 2025)
This research is literature research which is grouped intensively, in detail and in depth. The data collection method used in this search is based on applicable regulations, legal deepening is one type of research that is useful for future legal knowledge needs. To analyze files from search developments, you can manage primary and secondary data and then analyze them in a quantitative way. Next, an assessment was carried out and the essence was obtained. This means that the existence of electronic instrument evidence is absolutely recognized